Gender and Attorney Negotiation Ethics - Art Hinshaw; Jess K. Alberts (Washington University Journal of Law & Policy, 2012)
Few studies of gender differences and legal ethics exist, and of these only a handful focus on gender and negotiation ethics. In light of the paucity of evidence on this topic, we decided to include gender as a component of a broader study of attorney negotiation ethics. This Essay sets forth and discusses our findings and hypotheses regarding gender and negotiation ethics. In Part II we explain the requirements of the professional rules of attorney conduct governing negotiation, and in Part III we discuss the study’s methodology and findings from the larger study. Part IV offers a detailed review of the literature related to the influence of gender on ethical decision-making. The data resulting from this study is presented in Part V, and in Part VI, we discuss potential explanations for our findings in addition to addressing our study’s limitations. In conclusion, Part VII makes several suggestions for further studies on this topic.
Keywords: Gender & amp; ethics; Negotiation; Legal ethics; ABA Model Rules of Professional Conduct; Empirical analysis; Surveys; Decision making; Legal profession